Analisis Kebutuhan Pengembangan E-Modul Berbasis Etnomatika Budaya Melayu Riau Pada Materi Bangun Ruang Sisi Datar - Nur Aziela; Maimunah Maimunah; Yenita Roza (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
The problems that often become student complaints are the difficulty of understanding abstract questions provided in textbooks facilitated by the school, in mathematics learning not all teachers connect the material being taught with contextual problems that exist around students, and also based on the results of researchers' interviews with field teachers. information was obtained that the teacher had never combined the theme of Riau Malay culture with the material being taught. Therefore, we need a solution by making a teaching material in the form of an e-module based on the Riau Malay culture. The purpose of this study was to analyze the need for ethnomatic-based e-modules by integrating Riau Malay culture for grade VIII students of SMP / MTs. The research method used is qualitative descriptive method. The subjects of this research were the mathematics teachers at MTs Fadhilah and the eighth grade students of MTs Fadhilah in Pekanbaru. Analysis of research data using Analysis Interactive Miles-Huberman which includes data reduction, data presentation, and making conclusions. The results obtained in this study are that it is necessary to develop teaching materials in the form of e-modules based on the ethnomatics of the Malay Malay culture of building material on the flat side of class VIII SMP / MTs.